The use of biosolids compost as a soil conditioner in newly reclaimed sandy soils - Abdel-azeim, M. M. (Cranfield University, 2002)
Egypts population was projected to increase from 20 million in the 1960s to 67 million by 2000. With this increase in the population, an increase in food production of 200% to 300% is become necessary to meet food demands. In addition to the increasing demand for food, the population increase will result in increased amounts of human wastes. This will, in tum, need to be disposed of in ways other than the traditional dumping in the nearest stream or the Nile River. It is therefore vitally important to utilize as much as possible of this human waste (biosolids) as an organic fertilizer and soil conditioner to increase sandy soil productivity in Egypt. Composting is recognized as a cost-effective environmentally sound process for treatment of biosolids, even though they may contain substances, which pose potential hazard to the environment or food chain. The aim of this study was therefore set out to develop a management strategy that used biosolids compost as a soil conditioner and fertilizer to increase their agronomic benefits and minimize their environmental impacts when applied to newly reclaimed sandy soil. The agronomic benefits and the environmental impacts of applying biosolids compost to sandy soil were identified through a series of glasshouse, pot, and incubation trials using tomatoes and grass crop. Tomato was chosen as it represents a vegetable with a high potential for heavy metals uptake and because of its world-wide important as vegetable crop. The results of this work showed that, compost application had the capacity to stimulate vigorous growth, nutritional status, production levels of tomato plants, 'and to increase N recovery by tomato plants compared to control. The major nutrient concentrations of N, P, and K in tomato leaves taken from plants grown on compost M.M. Abdel-azeim, Ph.D. Thesis, 2002. The stem radius of tomato plants grown on the compost amended-plots were about twofold thicker in the case of the highest compost application rate (360 t/ha) than the plants from control plots. At 360 t/ha application rate, the tomatoes production level response for the compost-treated plots was 13.3 kg/plot while it was 1.8 kg/plot for the control. This represents an increase of more than 700% over the control plots. Nitrogen recovered by tomato crop following compost addition exceeded 20% of the total applied N after one and two compost applications. All these improvements in growth quality parameters of tomato plants were not significantly different at the higher compost application rates of 240 and 360 t/ha. This finding indicates that the plant response due to the increasing of compost application rate is subject to diminishing returns. The incorporation of biosolids compost into sandy soil has established sufficient grass covering area and improved soil aggregate stability compared to mulched-applied compost. The range in grass covering was a low of 7.9% for the control to 100% for incorporated applied compost at all application rates. The grass covering ranged from 7.9% for the control to 70% for mulched applied compost at the highest application rate. Incorporated-applied compost had more large aggregates and less small aggregates and consequently the overall aggregate stability ranged from 25 to 30% compared to 6 to 11% in the case of mulched-applied compost. The superiority of the incorporated-applied compost to the mulched-applied compost on aggregate stability was due to the stabilizing effects of the organic matter. The N mineralization rate has suggested that rapid and extensive N accumulated in the soil solution soon (60 days) after compost addition and the amount of N recovered was in excess of 20% of the total applied N. This value is higher than the 10% value reported elsewhere in the literature. Soil analysis of the compost treated plots revealed significant increases in soil pH, organic matter, CEC, soluble salts, and total heavy metals compared to control. Major considerations in recycling of biosolids compost on newly reclaimed sandy soils are the increase in soluble salts, the groundwater contamination by nitrate M.M. Abdel-azeim, Ph.D. Thesis, 2002. The increase in soluble salts following compost addition was at a level that could reduce yields in sensitive crops. High application rates of compost at high moisture status resulted in high levels of nitrate in the soil solution (> 50 mg/l). Another concern was the increased amounts of heavy metal accumulation in the soil profile where more than 90% of the compost- applied heavy metals were present in the top 20 cm of soil plots, but these increased amounts were still far below the plant toxicity levels. The results of this study clearly indicated that incorporated biosolids compost does increased agronomic benefits and does not pose the same environmental problems as mulched biosolids compost when used as a fertilizer with large-scale application rate. Application of biosolids compost significantly increased the concentration of heavy metals in tomato fruit compared to control. Crop recovery of compost-applied Zn and Cu by tomato plants was less than 0.5% at all compost application rates regardless of the method of application, and was significantly greater by tomato plants grown on compost-mulched plots than incorporated. Crop recovery of compost-applied Ni, Pb, Cd, and Cr by tomato plants was less than 0.08% at all compost application rates. In general, no health problems could be foreseen to humans or animals from food chain movement of these negligible amounts of heavy metals. With regard to heavy metal concentrations in the soil leachate, the data gave wide assurance that the environment is successfully protected. From this study, it could be concluded that high loading rates of good quality compost to sandy soils is ergonomically valuable with limited potential environmental risk if managed properly. Under the conditions of this study, incorporation of biosolids compost into sandy soil using drip irrigation system was the best management strategy practice to reach optimum agronomic benefits while minimizing environmental impacts. M.M. Abdel-azeim, Ph.D. Thesis, 2002.